Hydrogenic potential of toothpastes and mouth antiseptics with desensitizing properties (Research, Society and Development, 2021)
Objective: To evaluate the pH of three different brands of toothpaste and antiseptic used to prevent and relieve tooth sensitivity. Materials and methods: Three different brands of dentifrices were used: Sensodyne PRO-enamel®, Colgate sensitive PRO-alívio®, and Colgate Total 12®, all commercially available. For data analysis, 5g of each brand was weighed on a precision analytical balance, then 15 ml of distilled water were added for later reading. Meanwhile, the antiseptics considered for the research were Elmex sensitive®, Sensodyne® and Colgate Total 12®. 40ml of each brand was used. The hydrogen ion potential (pH) was measured by the metric potential method in a digital pH meter. The tests were performed in quintuplicate and the data analyzed by ANOVA/one-way with a significance level of 5%. Results: The dentifrice pH values ​​ranged between 7.95 ± 0.05 (Colgate Total 12®) and 9.71 ± 0.06 (Colgate sensitive PRO-alívio®), with a significant difference between all brands evaluated (p 0.05). But Sensodyne® had a higher and neutral pH and with a significant difference when compared to the two previous brands (p